Josiah Ober. The Rise and Fall of Classical Greece. - Bintliff, John (Journal of Greek Archaeology, 2017)
This book has already achieved major publicity both within Ancient History and also with a wider educated public, since it clearly takes a different tack from preceding summaries of Classical Greek history. Its historiography helps to account for this. Josiah Ober was well-known for research into the fortifications and defence of Classical Attica and also for studies of Athenian democracy. However when he came under the influence of a particular trend in Economic History, especially moving from the east of the States to Stanford, this source of inspiration grew into an ideological flood. Ober now significantly possesses a Chair in Political Science and Classics at Stanford and works closely with luminaries such as Ian Morris and Walter Scheidel. These latter colleagues have favoured the approach known as the New Institutional Economic History on the one hand, and on the other a broadening out into high-profile Global History (notably in books such as Morris’ Why the West Rules of 2010, and Scheidel’s Rome and China of 2009).